The Influence Of Entrepreneurial Self-Efficacy And Perceived Attractiveness On Entrepreneurial Intention: The Moderating Role Of Learning Orientation - Handri Dian Wahyudi; Agus Hermawan; Naswan Suharsono (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to empirically examine the influence of students’ entrepreneurial self-efficacy and perceived attractiveness on their entrepreneurial intentions and investigates the moderating role of students’ learning orientation. It considers how learning orientation may moderate the instrumentality of their perceived attractiveness to become a successful entrepreneur. The data used to test the hypotheses were obtained through an online survey issued to undergraduate students in business currently studying at a public college in Indonesia. Data received from 325 respondents is used to investigate the hypothesized correlations using the partial least squares structural equation modeling technique (PLS-SEM). The results show that students’ entrepreneurial self-efficacy and perceived attractiveness affect entrepreneurial intentions. A supplementary examination reveals the moderating effects of learning orientation on the connection between perceived attractiveness and entrepreneurial inclination. Moreover, the impact of learning orientation on the perceived attractiveness and intention relationship suggests that policymakers should give priority to the consideration of learning orientation when developing their strategies.